Berberine Modulates LPA Function to Inhibit the Proliferation and Inflammation of FLS-RA via p38/ERK MAPK Pathway Mediated by LPA1. (3rd November 2019) - Wang, Hui; Tu, Shenghao; Yang, Sisi; Shen, Pan; Huang, Yao; Ba, Xin; Lin, Weiji; Huang, Ying; Wang, Yu; Qin, Kai; Chen, Zhe
Abstract : Objective . This study aimed to investigate whether berberine exerted anti-inflammatory and antiproliferative effects on the fibroblast-like synoviocytes of rheumatoid arthritis (FLS-RA) through regulating the lysophosphatidic acid (LPA) function. Methods . Firstly, the expression levels of LPA and lysophosphatidic acid receptor 1 (LPA1 ) in RA patients, osteoarthritis (OA) patients, and healthy controls were detected. Moreover, molecular docking was employed to characterize the binding sites of berberine in the predicted protein targets. Later, FLS-RA were stimulated using berberine, LPA, and the specific inhibitor (Ki16425) of LPA1, thereafter, the effects on the proliferation, apoptosis, the release of inflammatory mediators of FLS-RA, and the MAPK pathway were observed. Results . Compared with healthy controls ( n = 25), the plasma LPA level ( n = 28) and synovial fluid ( n = 10) were markedly higher in RA patients. LPA1 was highly expressed in RA patients ( n = 4) relative to that in OA patients ( n = 4). Berberine remarkably inhibited the proliferation and the excessive production of IL-6 and TNF- α in FLS-RA, whereas suppressing the expression of K-ras, c-Raf, and p-38/ERK-phosphorylation. In addition, berberine inhibited the LPA-induced p-38/ERK-phosphorylation through binding to LPA1 . Conclusions . LPA plays a certain role in promoting the proliferation and inflammation of FLS-RA. Berberine potentially modulates LPA function to suppress the proliferation and inflammation of FLS-RA through blocking the p38/ERK MAPK pathway mediated by LPA1 . These findings suggest that, berberine possesses potential lipid-regulating, antiarthritis, and synovial hyperplasia inhibition activities against RA, which may provide a promising therapeutic target for the clinical drug development for RA patients with dyslipidemia and high CVD risk.